“Money politics” and “ethnicity” in voting decisions during Tanzania presidential election - Charles, Mwidima Peter; Mus Chairil Samani, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study sought to examine the influence of “money politics” in the voting decisions amongst voters in Tanzania. It was carried out immediately after the 2015 general election in the country. It sought to answer the problem using a qualitative research approach which used four Focus Group Discussions (FGD) to collect data. The informants of the study were selected from the districts of Ilemela and Nyamagana in Mwanza Tanzania. Each group comprised of 12 participants who were purposefully selected. These informants were selected because they had participated in the Tanzania general election. The method was chosen because it offers a mean to explore people’s experiences and opinions. A thematic analysis was used to analyse and manage the data whereby all necessary cleanings, transcription, coding, organizing, and theme were observed in the process. The findings reveal that ethnicity has a slight influence (54%) in the voting decisions amongst voters in Tanzania compared to money politics (46%). The findings further reveal that women voters in Tanzania are more influenced (63%) by money politics than men (37%), likewise, men voters are more influenced (57%) by ethnicity in their voting decisions and preferences than women. The findings indicate ethnicity and money politics are important predictive variables in determining the outcome of an election.